Advertising and design : interdisciplinary perspectives on a cultural field - Flath, Beate; Klein, Eva (Cultural and media studies., 2014)
The cultural field of advertising is a much-debated topic with perspectives focusing on a range of concepts from harassment and the anxiety of influence to notions of desire and affirmation. The aim of this publication is not only to take into account the diversity of topics related to advertising, but more importantly, to develop a dialogue between these divergent viewpoints. With contributions by Barbara Aulinger, Bernadette Collenberg-Plotnikov, Beate Flath, Werner Jauk, Bernhard Kettemann, Eva Klein, Jörg Matthes, Manfred Prisching, Johanna Rolshoven, Nicolas Ruth, Holger Schramm, Charles Spence, Margit Stadlober and Friedrich Weltzien.